The Physical and Biochemical Characteristics of Resistance in Different Rice Varieties and Initial Moisture Content for Their Susceptibility to Rhyzopertha dominica F. (Coleoptera: Bostrichidae) - ASTUTI, Ludji Pantja; MUDJIONO, Gatot; RASMINAH, Siti Ch.; RAHARDJO, Bambang Tri (Walailak Journal of Science and Technology (WJST), 2021)
Rhyzopertha dominica reduces the weight of rice production at approximately 40 %. This study aimed to investigate the physical and biochemical characteristics of resistance in different rice varieties at different initial moisture content to their susceptibility against R. dominica. The study consisted of 2 experiments: (i) free-choice, and (ii) no-choice tests. These experiments were conducted by combining 6 rice varieties (Vi): IR-64, Ciherang, Membramo, Cibogo, Sembada, and, Intani-2, and 4 levels of initial moisture content (Ki): 10, 12, 14, and 16 %. The observed variables for the free-choice test were the number of adult insects (male and female) present, the number of females present, and the percentage of weight loss. The observed variables for the no-choice test were the number of eggs, larvae, F1 progeny emerged, and the median developmental time of R. dominica. Results of the free-choice test revealed that the highest total number of adult insects present, the female insects present, and the percentage of weight loss appeared in the Intani-2 variety at 16 % initial moisture content, while the lowest of these 3 variables appeared in the Membramo variety at 10 % initial moisture content. The no-choice test revealed that the rice varieties became more susceptible with the increase of the initial moisture content. The susceptibility of rice was affected by hardness, ash content, and phenol content. Rice hardness level were caused by the level of initial moisture content. However, the chemical characteristics of the rice were not affected by the level of initial moisture content.